Pasto varnish: 3D virtualization of an intangible cultural heritage - Carlos Córdoba-Cely; Arturo de la Cruz (Virtual Archaeology Review)
The artisanal technique of "barniz de Pasto" (Pasto varnish) in Colombia is an example of an Intangible Cultural Heritage (ICH) that requires urgent safeguarding processes due to a number of factors, including weakened practices, disrupted transmission, and environmental deterioration. The term "Pasto varnish" refers to an ancient artistic tradition from southern Colombia, which was designated as an Intangible Cultural Heritage (ICH) by UNESCO in 2020. This technique entails the decoration of diverse surfaces, including metal and wood, through the application of a thin, malleable film of natural resin derived from the mopa-mopa shrub (Elaeagia pastoensis L.E. Mora), which exhibits the capacity to adhere to a range of surfaces. This article presents the results of the 3D virtualization process of 22 heritage pieces from this technique, which are exhibited on the Virtual Pasto Varnish (VPV) website. The construction of this website entailed the implementation of three domains of virtualization: (i) 3D Documentation, wherein data pertinent to the heritage were collated; (ii) 3D Representation, wherein 3D material corresponding to the heritage artifact was created; and (iii) 3D Dissemination, which facilitated the dissemination and conservation of the 3D data. The results of this project demonstrate that virtual heritage can serve as a collaborative instrument for the integration, safeguarding, and promotion of research on ICH through the data, paradata, and metadata obtained during the 3D virtualization process. This article puts forth the proposition that virtual heritage makes significant contributions to ICH, particularly in regard to the continual recreation of living heritage through self-recognition, the dynamic conservation of its artifacts, and the contextualized research of its data. It can be concluded that for ICH materialized in artifacts—such as the case of Pasto varnish—virtual heritage becomes an important preservation tool when tradition bearers can be actively engaged in the process of "reviving the aura" of the heritage data.